How to Hire and Manage Residential Contractors - Randall A. Cantrell (EDIS, 2013)
If you are looking for a contractor for either home building or remodeling, ask difficult questions before you enter into a contract. This way you and the contractor have a clear understanding of the other’s expectations. Before signing a contract and beginning a project is the best time to thank contractors for their consideration and time, rather than risk entering into an unfortunate working relationship that could require legal intervention. Contractors understand potential clients, and they will inform you if they do not want to accept a contract with you. This negotiation period should not be taken personally by either party and should only develop into a business relationship that exists during the period of hire and warranty outlined in the contract. This 5-page fact sheet was written by Randall A. Cantrell, and published by the UF Department of Family Youth and Community Sciences, September 2013.